Temperature effect and compensation scheme for tunable ultra-high-resistance pseudo resistor. (August 2020) - Mohamed, Ahmed Reda; Wang, Guoxing
Abstract: Pseudo resistors with ultra-high resistance implemented using MOSFETS are employed in a wide range of biomedical applications. However, their resistances are highly dependent on temperature. A gate-voltage-controlled pseudo resistor is proposed to compensate the temperature impact through trimming. Simplified models have been proposed for analyzing the pseudo resistor, and a linear trimming scheme is proposed. The proposed tunable pseudo resistor is fabricated and measured in standard 0.35 μm CMOS technology. Experimental results demonstrated that tuning could adequately compensate the temperature-induced resistance variation by 8.75x and provide relatively low-temperature dependence.